Case Report: Preservation of Otolithic Function After Triple Semicircular Canal Occlusion in a Patient With Intractable Ménière Disease - Zhang, Yuzhong; Cheng, Ying; Chen, Zichen; Chen, Feiyun; Zhang, Qing (Frontiers in Neurology, 2021)
Operative measures are considered when medical treatment fails to control vertigo in patients with intractable Ménière disease. The present report discusses a case in which triple semicircular canal occlusion was performed in a 30-year-old female patient who responded poorly to previously performed endolymphatic sac surgery. Her vestibular and auditory functions were evaluated both before and after surgery. Class A control of vertigo was achieved during the 76-month postoperative follow-up period. Ocular and cervical vestibular evoked myogenic potentials could be elicited before and after surgery. This case suggests that relatively long-term preservation of otolithic function can be achieved following triple semicircular canal occlusion, highlighting its potential as an alternative treatment for patients with Ménière disease.